2018
DOI: 10.7897/2230-8407.09690
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Free Radical Scavenging Activity of Rhizophora Mucronata Lamk. Bark Extracts From Kendari Bay of Southeast Sulawesi Province Indonesia

Abstract: The aim of this study was to evaluate the toxicity and free radical scavenging activity of Rhizophora mucronata Lamk. bark extracts from the mangrove forest of Kendari Bay, Southeast Sulawesi Province Indonesia. The extracts were obtained by maceration of R. mucronata Lamk. bark with n-hexane, ethyl acetate, and methanol, respectively. Toxicity test was conducted by using Brine Shrimp Lethal Test (BSLT) method with Artemia salina Leach as the animal test, while free radical scavenging activity test was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Lamk. We previously have reported toxicity and anti-oxidant activity of the bark extracts 11 . In this study, we reported the isolation and cytotoxic assessment of α-amyrin and β-sitosterol compounds from an n-hexane extract of the bark of R. mucronata against HeLa cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Lamk. We previously have reported toxicity and anti-oxidant activity of the bark extracts 11 . In this study, we reported the isolation and cytotoxic assessment of α-amyrin and β-sitosterol compounds from an n-hexane extract of the bark of R. mucronata against HeLa cell line.…”
Section: Introductionmentioning
confidence: 99%